Implementation of Milk Run Theory for Enhanced Logistics Efficiency: A Case Study in the Plastic Packaging Manufacturing - Soesilo, Rahman; Valentin, Adelia Dwi (Krisnadwipayana International Journal of Management Studies, 2024)
This research investigates the impact of implementing the Milk Run method in the plastics industry supply chain, focusing on PT RPI. By reducing the distance by 48 km per day, equivalent to 1,200 km in one month of deliveries, the results are significant in terms of logistics efficiency, cost savings, and reduced carbon emissions. Logistics are improved with more connected travel patterns, allowing trucks to combine pickups or deliveries from multiple sources in a single trip. Distance reduction strengthens transportation cost efficiency by reducing fuel consumption and vehicle maintenance costs. Assuming a fuel consumption rate of 7 km per liter and carbon emissions of 2.68 kg CO2 per liter, a distance reduction of 1,200 km results in a substantial reduction in carbon emissions. This study provides a foundation for future research, including route and scheduling optimization, in-depth environmental impact analysis, and application of the Milk Run to other industries. The results provide a complete picture of the effectiveness of the Milk Run in the context of the plastics industry, highlighting operational excellence, economic impact and the company's commitment to sustainability